2019
DOI: 10.5812/msnj.98762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eye Masks, Earplugs, and Quiet Time Protocol on Sleep Quality of Patients Admitted to the Cardiac Care Unit: A Clinical Trial Study

Abstract: Background: There are several factors such as noise and light, which affect the sleep quality of patients admitted to the cardiac care unit (CCU) and cause sleep disorders in these individuals. Objectives: The purpose of this study was to compare the impact of applying eye masks and earplugs as well as implementing the quiet time (QT) protocol on the sleep quality of patients hospitalized in the CCU of Ali Ibn Abi Talib Hospital in Zahedan. Methods: This clinical trial was performed on 135 CCU patients. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…VSH was used in various modifications in 3 studies. Tabas et al [26], Yazdannik et al [5], and Bajwa et al [17] used its 16-item version. The first study confirmed the statistical improvement in subjectively perceived sleep quality in all three subscales (discomfort, efficacy, support) ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…VSH was used in various modifications in 3 studies. Tabas et al [26], Yazdannik et al [5], and Bajwa et al [17] used its 16-item version. The first study confirmed the statistical improvement in subjectively perceived sleep quality in all three subscales (discomfort, efficacy, support) ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The findings from this study are supported by a similar study by Arttawejkul et al [ 19 ] that demonstrated a decrease in the arousal index and improved activity index among patients who received earplugs and eye masks for the first five nights in the ICU, compared with a control group. A clinical trial among 135 critical care unit (CCU) patients for three days after admission revealed that the institution of a quiet environment protocol and the use of simple, noninvasive, and cost-effective measures of earplugs and eye masks were beneficial for decreasing sleep disturbance and improving sleep efficacy, thereby improving sleep quality compared with the control group [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a similar study (Ebrahimi Tabas et al) (32) and using the following formula, the sample size was estimated as 18 subjects per group with a 95% confidence interval and 95% test power. However, given the possibility of the participants' dropout, the sample size was considered 20 subjects per group (40 participants in total) as follows: The criteria for enrolment in the study were being alert and aware of time and place (the Glasgow Coma Scale [GCS] ≤ 12), absence of hearing and vision disorders, absence of history and habit of using eye masks and earplugs, absence of drug use at night, and non-prohibition of massage for the patient.…”
Section: Methodsmentioning
confidence: 99%